Biogenic habitat transitions influence facilitation in a marine soft‐sediment ecosystem - Andrew M. Lohrer; Iván F. Rodil; Michael Townsend; Luca D. Chiaroni; Judi E. Hewitt; Simon F. Thrush (Ecology, 2013)
Habitats are often defined by the presence of key species and biogenic features. However, the ecological consequences of interactions among distinct habitat‐forming species in transition zones where their habitats overlap remain poorly understood. We investigated transition zone interactions by conducting experiments at three locations in Mahurangi Harbour, New Zealand, where the abundance of two habitat‐forming marine species naturally varied. The two key species differed in form and function: One was a sessile suspension‐feeding bivalve that protruded from the sediment ( Atrina zelandica ; Pinnidae); the other was a mobile infaunal urchin that bioturbated sediment ( Echinocardium cordatum ; Spatangoida). The experimental treatments established at each site reflected the natural densities of the species across sites ( Atrina only, Echinocardium only, Atrina and Echinocardium together, and plots with neither species present). We identified the individual and combined effects of the two key species on sediment characteristics and co‐occurring macrofauna. After five months, we documented significant treatment effects, including the highest abundance of co‐occurring macrofauna in the Atrina ‐only treatments. However, the facilitation of macrofauna by Atrina (relative to removal treatments) was entirely negated in the presence of Echinocardium at densities >10 individuals/m 2 . The transitional areas in Mahurangi Harbour composed of co‐occurring Atrina and Echinocardium are currently widespread and are probably more common now than monospecific patches of either individual species, due to the thinning of dense Atrina patches into sparser mixed zones during the last 10–15 years. Thus, although some ecologists avoid ecotones and habitat edges when designing experiments, suspecting that it will skew the extrapolation of results, this study increased our understanding of benthic community dynamics across larger proportions of the seascape and provided insights into temporal changes in community structure associated with patch dynamics. Particularly in situations where non‐abrupt habitat transitions are commonplace, documentation of community dynamics in individual biogenic habitats and in mixed transition zones is required in order to scale‐up and generalize results.